2022
DOI: 10.1530/eje-22-0263
|View full text |Cite
|
Sign up to set email alerts
|

Global psychological assessment with the evaluation of life and sleep quality and sexual and cognitive function in a large number of patients with acromegaly: a cross-sectional study

Abstract: Objective: Acromegaly is associated with somatic disfigurements which impair self-perception of well-being and quality of life. Nowadays limited data are available on the interplay between hormonal excess and psychological discomfort. The study aimed at investigating the psychological profile, sleep quality, sexual function, cognitive functions, and quality of life in acromegaly. Methods: in 223 acromegaly patients from five referral centres global psychological profile, sleep quality, sexual function, cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 113 publications
0
9
1
Order By: Relevance
“…In the recent decade, cumulative studies have provided different perspectives for the investigation of cognitive impairment in acromegalic patients at various disease stages—from the naïve status, under therapeutic options, to controlled or even long-term remission [ 17 , 18 , 19 ]. Nevertheless, conflicting outcomes have emerged regarding cognitive functions.…”
Section: Historical Perspectivementioning
confidence: 99%
See 4 more Smart Citations
“…In the recent decade, cumulative studies have provided different perspectives for the investigation of cognitive impairment in acromegalic patients at various disease stages—from the naïve status, under therapeutic options, to controlled or even long-term remission [ 17 , 18 , 19 ]. Nevertheless, conflicting outcomes have emerged regarding cognitive functions.…”
Section: Historical Perspectivementioning
confidence: 99%
“…In two studies with a heterogeneous population of acromegaly patients, the prevalence rate of cognitive impairment varied between 10 and 72% [ 19 , 27 ]. In a cross-sectional study of 55 patients with acromegaly [ 27 ], Sievers et al found that cognitive impairment was prevalent in patients, with 67.3% of patients not meeting the critical levels on at least one test; more specifically, up to 33.3% had impaired attention, 24.1% had memory impairment, and 16.7% had poor executive function performance.…”
Section: Cognitive Impairments In Acromegalymentioning
confidence: 99%
See 3 more Smart Citations